(NgLUBINY PRONIKNOWENIQ RAZLOMOW (B/s - (NsANXKOW(B, (NwLADIMIR aNATOLXEWI^s; (N{ERMAN(B, (Ns(B. (Ni(B.s ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 121-135s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NiN(B-(NT ZEMNOJ KORYs
Keywords: (NrAZLOMY GLUBINNYEs